Numerical modelling of soil arching in a shallow backfill layer = Modelowanie numeryczne przesklepienia gruntu w płytkiej warstwie zasypki - Szajna, Waldemar St. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the application of the finite element method into the modelling of soil arching. The phenomenon plays fundamental role in soil-shell flexible structures behaviour. To evaluate the influence of arching on a pressure reduction, a plain strain trapdoor under a shallow layer of backfill was simulated. The Coulomb-Mohr plasticity condition and the nonassociated flow rule were used for the soil model.
Keywords: przesklepienie; konstrukcja gruntowo-powłokowa; problem zapadni; redystrybucja naprężeń; MES; model Coulomba-Mohra; arching; soil-shell structure; trapdoor problem; stress redistribution; FEM; Mohr-Coulomb model